Concise Synthesis and Facile Nanotube Assembly of a Symmetrically Multifunctionalized Cycloparaphenylene. Issue 52 (16th November 2015) - Miyauchi, Yuta; Johmoto, Kohei; Yasuda, Nobuhiro; Uekusa, Hidehiro; Fujii, Shintaro; Kiguchi, Manabu; Ito, Hideto; Itami, Kenichiro; Tanaka, Ken
Abstract: The concise synthesis of C 3 ‐symmetrical [12]CPP‐hexacarboxylate has been achieved through macrocyclization by the rhodium‐catalyzed intermolecular cross‐cyclotrimerization and subsequent reductive aromatization. C 3 ‐Symmetrical functionalization of CPP with highly polar alkoxycarbonyl groups enabled the structurally uniform nanotube assembly in the crystalline state through multiple hydrogen‐bonding interactions giving a dimer followed by one‐dimensional stacking. Abstract : Rhod to nanotubes ! The concise synthesis of a symmetrically multifunctionalized cycloparaphenylene (CPP), C 3 ‐symmetrical [12]CPP‐hexacarboxylate, has been achieved by rhodium‐catalyzed macrocyclization and subsequent reductive aromatization (see scheme). C 3 ‐Symmetrical functionalization of CPP with highly polar alkoxycarbonyl groups enabled the facile nanotube assembly on the flat solid surface as well as in the crystalline state.